Seed and seed coat morphology in monotypic and endemic genera of Korean angiosperms - Se-moon Ahn; Hye-rin Kim; Kweon Heo (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2023)
The basic information of ovule and seed characteristics was investigated for five monotypic and endemic genera in the Korean peninsula as categorized by the Flora of Korea category. The carpels and seeds were sectioned with a rotary microtome. Mature seeds were coated with platinum using an ion sputter and observed using a scanning electron microscope. As a result, Abeliophyllum was found to be anatropous and a unitegmic ovule, with a slightly colliculate seed surface and exotestal seed coat type. The ovule of Coreanomecon was anatropous and bitegmic, having a distinct echinate seed surface, and exo-endotestal seed coat type with a prismatic crystal in the mesotesta. The ovule of Hanabusaya was anatropous and a unitegmic, with a long reticulate seed surface sculpture, and distinct exotestal seed coat type. In addition, a wing developed at the opposite side of the raphe bundle. Megaleranthis was an anatropous and bitegmic ovule, having a small pentagonal disk shape, a concave seed surface and exotestal seed coat type. Finally, Pentactina was also anatropous and a unitegmic ovule, reticulate seed sculpture, and endotestal seed coat type. These data will be proving to be a source of good information for securing bio-sovereignty in the near future.